2020
DOI: 10.1108/dprg-08-2020-0101
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization and migration: the role of social media and migrant networks in migration decisions. An exploratory study in Nigeria

Abstract: Purpose This paper aims to explore the connectivity between social media use, access to migrant networks, information asymmetry and migration intentions. Design/methodology/approach The study was conducted using data from individuals living in Nigeria and analysed with a generalized structural equation model, which is rare for this kind of research. Findings The authors find a dual mediating role of the social media and the migrant networks in facilitating migration, i.e. reducing the threshold cost requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
2
8
0
5
Order By: Relevance
“…Hence, they feel disappointed about not reaching these and report lower life satisfaction as they are faced with initial problems with bureaucracy, which deprive them of opportunities for achieving their objectives. Secondly, in terms of bounded rationality, it is possible that the challenge of incomplete information and misinformation about the realities in Europe, which make most Nigerians overestimate the economic opportunities and living conditions in Italy and Europe (Brunarska, 2019;Obi et al, 2020), causes them to report lower SWB when they are confronted with realities. However, we cannot single out these effects with the cross-sectional data.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, they feel disappointed about not reaching these and report lower life satisfaction as they are faced with initial problems with bureaucracy, which deprive them of opportunities for achieving their objectives. Secondly, in terms of bounded rationality, it is possible that the challenge of incomplete information and misinformation about the realities in Europe, which make most Nigerians overestimate the economic opportunities and living conditions in Italy and Europe (Brunarska, 2019;Obi et al, 2020), causes them to report lower SWB when they are confronted with realities. However, we cannot single out these effects with the cross-sectional data.…”
Section: Discussionmentioning
confidence: 99%
“…Migrants rely on digital tools when planning their migration trajectories (Dekker et al , 2018; Gelb and Krishnan, 2018; Gillespie et al , 2018; Nedelcu and Soysüren, 2020; Obi et al , 2021) and creating support networks (Almenara-Niebla and Ascanio-Sánchez, 2019; Patterson and Leurs, 2019). There are two important aspects that must be subjected to a brief examination to contextualise and situate the findings of the research presented in the following sections: the problems of exclusion and Western bias in technological social innovations development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Technology and the migration journey have become increasingly fused together over the past decades, with smart migrants and refugees crossing smart borders and making use of information and communications technology (ICT) tools to reap the benefits of e-governance (Dekker et al , 2018; Nedelcu and Soysüren, 2020; Pötzsch, 2018; Obi et al , 2021). Within these processes, however, numerous ethical, legal and practical concerns arise – from the intrusive surveillance of migrants, to the use of artificial intelligence (AI; Molnar, 2019, 2022; Beduschi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Alexander et al (2020), using Bayesian models, concluded that social media increases remittances. Obi et al (2021) found that social media and access to migrant networks directly increase migration intentions as well as remittances to Nigeria. Recently, Kalantaryan et al (2022), using data from the Facebook Social Connectivity Index, found that the social network Facebook has significantly increased remittances in five European countries over the period 2010-2018.…”
Section: Social Media and Remittances: Empirical Synthesismentioning
confidence: 99%